2014
DOI: 10.1021/jo500759a
|View full text |Cite
|
Sign up to set email alerts
|

Triflic Acid Promoted Direct α-Alkylation of Unactivated Ketones Using Benzylic Alcohols via in Situ Formed Acetals

Abstract: Direct α-alkylation of unactivated ketones using benzylic alcohols as electrophiles has been achieved at room temperature. This reaction takes place via in situ formed acetal using triflic acid and trimethyl orthoformate. It is believed that methyl vinyl ether formed from the in situ generated dimethyl acetal in the presence of triflic acid undergoes alkylation. Diverse ketones could be alkylated with diarylmethanols, cinnamyl alcohols, and phenyl propargyl alcohols having different electrophilicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…For instance, in the addition of active aldehyde and diarylmethanols, 20 mol % TfOH was used to activate bis(4‐chlorophenyl)methanol to obtain a moderate ∼53 % yield of the α‐alkylation product; for poorly active ketones an increased amount of TfOH had to be used (1 equiv.) along with trimethyl orthoformate . It is believed that TfOH promoted the in situ generation of dimethyl acetal to facilitate the smooth generation of methyl vinyl ether.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the addition of active aldehyde and diarylmethanols, 20 mol % TfOH was used to activate bis(4‐chlorophenyl)methanol to obtain a moderate ∼53 % yield of the α‐alkylation product; for poorly active ketones an increased amount of TfOH had to be used (1 equiv.) along with trimethyl orthoformate . It is believed that TfOH promoted the in situ generation of dimethyl acetal to facilitate the smooth generation of methyl vinyl ether.…”
Section: Introductionmentioning
confidence: 99%
“…In our efforts to develop organic transformations using in‐situ‐formed acetals,6 we found that alkyl ketones generate enol ethers via in‐situ‐formed acetals under Lewis/Brønsted acidic conditions in the presence of trimethyl orthoformate. It was demonstrated that the formed enol ether could be alkylated directly with various alcohols using either triflic acid (TfOH)6d or AgSbF 6 6e. Recently, we reported an acetal‐assisted intermolecular alkyne–carbonyl metathesis and intramolecular annulation between o ‐alkynylbenzaldehydes and alkynes in the presence of trimethyl orthoformate and catalytic Brønsted acid for the synthesis of substituted benzo[ a ]fluorene derivatives 6c.…”
Section: Introductionmentioning
confidence: 99%
“…This can easily be understood from the limited substrate scope of diarylmethanols in the alkylation reactions with ketones 3e,4e. In our research endeavours to utilize in situ formed acetals6 we have found that a stoichiometric amount of TfOH is able to promote the direct α‐alkylation of different ketones with a wide range of benzylic alcohols at room temperature 6c. The success of the reaction is due to the formation of methyl vinyl ether from the ketone via an in situ generated acetal formed by the reaction of trimethyl orthoformate with the ketone in the presence of triflic acid 7.…”
Section: Introductionmentioning
confidence: 99%